Health Status Determinants in the OECD Countries. A Panel Data Approach with Endogenous Regressors. - Ana Pocas; Elias Soukiazis (European Regional Science Association (ERSA), 2010)
The purpose of this study is to analyse the determinants of life expectancy as proxy for health status of the OECD countries' population. A production function of health is used to explain expectancy life at birth for total and ageing population and according to gender. Socio-economic factors, health resources and lifestyles are defined as the main determinants of heath status. The estimation approach assumes that income and education are endogenous and a panel data approach is used to control for this problem. Our evidence shows that income, education and efficiency of health resources of the health system are important factors affecting positively life expectancy and risky lifestyles (tobacco and alcohol consumption) are harmful to health. However there are differences between males and females. Income and lifestyles are the major determinants affecting man's health while for women education and better use of health services (through consultations) explain mostly life expectancy both at birth and late age.
Keywords: H51; I12; I18; C23; 330; health status; production funtion of health; endogeneity; panel data